Neuroanatomical Basis of State-Dependent Activity of Upper Airway Muscles - Rukhadze, Irma; Fenik, Victor B. (Frontiers in Neurology, 2018)
Obstructive Sleep Apnea (OSA) is a common sleep-related respiratory disorder that is associated with cognitive, cardiovascular and metabolic morbidities. The major cause of OSA is the sleep-related reduction of upper airway muscle tone that leads to airway obstructions in individuals with anatomically narrow upper airway. This reduction is mainly due to the suppressant effect of sleep on hypoglossal motoneurons that innervate upper airway muscles. The hypoglossal motoneurons have state-dependent activity, which is decreased during the transition from wakefulness to non-rapid eye movement sleep and is further suppressed during rapid eye movement sleep. Multiple neurotransmitters and their receptors have been implicated in the control of hypoglossal motoneuron activity across the sleep-wake states. However, to date, the results of the rigorous testing show that withdrawal of noradrenergic excitation and cholinergic inhibition essentially contribute to the depression of hypoglossal motoneuron activity during sleep. The present review will focus on origins of noradrenergic and cholinergic innervation of hypoglossal motoneurons and the functional role of these neurons in the state-dependent activity of hypoglossal motoneurons.